2020
DOI: 10.18089/tms.2020.160202
|View full text |Cite
|
Sign up to set email alerts
|

Coastal tourism development in Sinop as an emerging rural destination: A preliminary study from the residents’ perspective

Abstract: This study proposes to explore the economic, sociocultural, and environmental effects of coastal tourism development in a Turkish context. It adopts a quantitative approach and performed a random sampling technique. The survey data was collected from a sample of local people in Sinop/Turkey and total number of 252 utilizable questionnaires was gathered and analyzed through descriptive statistics. ANOVA test was also applied in order to compute the perceptional differences among demographical groups. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…For example, focusing on the social effects of tourism development, a recent study carried out in Besalú, Catalonia, Spain [ 41 ] revealed that the greatest consensus disagree was related to the negative effects on higher crime rates and the tourism-related noise, while the greatest consensus on positive statements was relevant to the fact that tourism brings jobs and preserve the cultural heritage. Similarly, although Daskin and co-authors [ 15 ] showed that residents had positive attitudes and perceptions towards the role of tourism on improving many sociocultural aspects, the authors underlined distinct negative impacts on the destination, such as the increase in travel accidents, illegal gambling and vandalism. Other studies showed that tourism in rural regions can support the participation of under-represented groups, such as the indigenous individuals and women [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, focusing on the social effects of tourism development, a recent study carried out in Besalú, Catalonia, Spain [ 41 ] revealed that the greatest consensus disagree was related to the negative effects on higher crime rates and the tourism-related noise, while the greatest consensus on positive statements was relevant to the fact that tourism brings jobs and preserve the cultural heritage. Similarly, although Daskin and co-authors [ 15 ] showed that residents had positive attitudes and perceptions towards the role of tourism on improving many sociocultural aspects, the authors underlined distinct negative impacts on the destination, such as the increase in travel accidents, illegal gambling and vandalism. Other studies showed that tourism in rural regions can support the participation of under-represented groups, such as the indigenous individuals and women [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it helps support the protection of the environment and wildlife [ 13 , 14 ]. For instance, Daskin et al [ 15 ] investigated the impact of rural tourism development in the coastal city Sinop in Turkey. Out of a five-point Likert scale score (1 to 5), the research group found the average value for positive environmental effects was 3.93 and for negative environmental effects was 2.58, which reflects the benefits of tourism to the renovation of the environment locally and the minimal negative impacts, respectively [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations